Development of energy generation model using robust partial least squares-structural equation modelling (RPLS-SEM) through winsorization method - Zulkifley Mohamed (Tanjong Malim, 2019)
Development of energy generation model using robust partial least squares-structural equation modelling (RPLS-SEM) through winsorization method by Zulkifley Mohamed